2019
DOI: 10.1093/trstmh/trz069
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic performance of rapid diagnostic tests and microscopy for malaria diagnosis in eastern Sudan using a nested polymerase chain reaction assay as a reference standard

Abstract: Background Accurate diagnosis of malaria infection is essential for successful control and management of the disease. Both microscopy and rapid diagnostic tests (RDTs) are recommended for malaria diagnosis, however, RDTs are more commonly used. The aim of the current study was to assess the performance of microscopy and RDTs in the diagnosis of Plasmodium falciparum infection using a nested polymerase chain reaction (PCR) assay as the gold standard. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
10
4
Order By: Relevance
“…However, recent studies have shown mRDT to be more reliable than microscopy. 41,42 In addition, collection of single slides for STHs might have biased the findings considering day-to-day variability of STH eggs excretion as well as in children with low intensity. Inclusion of schoolchildren present on the day of the survey may introduce minimal selection bias; however, our study team did community sensitization through school, ward, and village meetings with leaders who communicated with the parents.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown mRDT to be more reliable than microscopy. 41,42 In addition, collection of single slides for STHs might have biased the findings considering day-to-day variability of STH eggs excretion as well as in children with low intensity. Inclusion of schoolchildren present on the day of the survey may introduce minimal selection bias; however, our study team did community sensitization through school, ward, and village meetings with leaders who communicated with the parents.…”
Section: Discussionmentioning
confidence: 99%
“…RDTs targeting HRP2 are specific for the detection of P. falciparum , while RDTs targeting LDH can be used for the detection of P. falciparum , P. vivax , or pan-specific (e.g., four Plasmodium species) LDH antibodies; aldolase is another common target for RDTs to detect all Plasmodium species 7 10 . Recently used commercial dipsticks for the detection of HRP-2 include PfHRP2 CareStart 11 13 , SD Bioline Malaria Ag Pf 14 , 15 , and SD BIOLINE Malaria Ag P.f/Pan 16 , and one recently used for the detection of pLDH is CareStart pLDH(pan) 15 . A recently used commercial dipstick for the detection of Pan-aldolase is ParaHit Total, while a recently used commercial dipsticks for the detection of P. vivax aldolase is mAb 1C3-12 F10 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy was not a good indicator due to the limitation that implies the imbalance of the test set (1 parasitized erythrocyte per every 4 healthy RBCs). Comparing the performance of the CNN to the gold standard, the microscopic analysis of stained blood films: NPV (84%) and specificity (87%) are similar to the gold standard (90.40% and 92.20%, respectively), but PPV (23%) and sensitivity are not (18%), as in the gold standard they are 69.80% and 74.30% [ 24 ]. It should be taken into account that the training and validation sets had the same origin (Malaria dataset from the LHNCBC) and the test set did not as it was part of the collection of images of the research group [ 14 , 25 ] and too small to be used also for training and validation.…”
Section: Discussionmentioning
confidence: 99%